Georgia : Skills Mismatch and Unemployment, Labor Market Challenges - World Bank (Washington, DC, 2013)
This paper reviews labor market performance in Georgia, and examines the link between labor market outcomes and poverty. At over 15 percent, the unemployment rate in the country is high by European standards. Georgia faces three main labor market issues: (a) underutilization of labor resources, (b) earnings inequality, and (c) skills mismatch. All three have a negative impact on poverty. There is a mismatch between the demand for highly educated workers and their supply. Improving labor market outcomes is key to poverty reduction. This requires supporting the creation of more and better jobs in order to absorb the surplus labor and increase earnings. It also requires improving the quality of education to reduce the skills mismatch and support modernization of the Georgian economy. Finally, improving labor market outcomes requires developing institutions that improve access to jobs, reduce income inequality, and effectively protect core worker rights. The analysis presented in this paper represents individual level data from the 2010 Household Budget Survey (HBS) implemented by the National Statistics Office of Georgia (Geostat).